2019
DOI: 10.5539/ijbm.v14n9p132
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Business Process Re-Engineering on Organizational Performance: The Mediating Role of Information and Communications Technology

Abstract: The purpose of this study is to attempt to highlight the factors of business process reengineering (BPR) processes that effect on organizational performance in the Drivers and Vehicles License Department (DVLD) in Jordan through using ICT as a mediating role. From previous studies, five factors of BPR were adopted for this study, including "Ability to change, Selecting BPR Methodology, Organizational Culture, BPR strategic alignment, and Top management support ". ICT was used as an intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The results of the study indicated a significant relationship between business process reengineering strategy and the performance of food manufacturing companies in Kenya. In a study conducted by Khashman (2019), the research aimed to highlight the factors of business process reengineering, including its dimensions (ability to change, selection of process reengineering methodology, top management support, organizational culture, and strategic alignment), that influence organizational performance in the management of driver and vehicle licensing in Jordan through the use of information and communication technology as an intermediary role.the study utilized the SMART PLS software to analyze the core relationships betweenthe most relevant variables related to business process reengineering, information and communication technology, and organizational performance across five structural models. The study's sample included all employees at operational, middle, and upper management levels, totaling 124 workers in the Driver and Vehicle Licensing Department.the results of the study revealed a strong and statistically significant positive relationship between several variables of business process reengineering and organizational performance when using information and communication technology as a mediating variable.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The results of the study indicated a significant relationship between business process reengineering strategy and the performance of food manufacturing companies in Kenya. In a study conducted by Khashman (2019), the research aimed to highlight the factors of business process reengineering, including its dimensions (ability to change, selection of process reengineering methodology, top management support, organizational culture, and strategic alignment), that influence organizational performance in the management of driver and vehicle licensing in Jordan through the use of information and communication technology as an intermediary role.the study utilized the SMART PLS software to analyze the core relationships betweenthe most relevant variables related to business process reengineering, information and communication technology, and organizational performance across five structural models. The study's sample included all employees at operational, middle, and upper management levels, totaling 124 workers in the Driver and Vehicle Licensing Department.the results of the study revealed a strong and statistically significant positive relationship between several variables of business process reengineering and organizational performance when using information and communication technology as a mediating variable.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The studies of (Dalalo and Hunde (2020); Jayawardane and Gamlath (2020); Yensu, Yiadom, and Awatey ( 2016)) all supported that a strategic focus on the business processes will all ultimately lead to a better financial performance. However, there are also studies that utilised secondary data and this is applicable in most cases reviewed to manufacturing organisations of public companies (Adefulu, Akinshipe, Makinde, & Akpa (2020); Bako & Banmeke (2020) ; Andari, Agustina, Mariana, & Fathonah (2019) ; Khashman, 2019;Ofurum et al, 2019;Olotu, Salawu, Adegbie, & Akinwunmi (2019) ; Otulia, Mbeche, Wainaina, & Njihia (2017).…”
Section: Empirical Review -Financial Re-engineering and Financial Per...mentioning
confidence: 99%
“…Nold prescribes the use of Information technology to challenge the assumption inherent in the work processes that have existed since long before the advent of modern computer and communication technology. Khashman (2019) identified Information and Communication Technology as a critical component of the business process reengineering process. Jovanoski, Malinovski and Arsenovski (2017) referred to this broadened, recursive view of Information Technology and Business Process Reengineering as the new industrial reengineering process, which represents a new approach to coordination across the firm.…”
Section: Statements Onmentioning
confidence: 99%